New hope for the treatment of recurrent and refractory psoriasis: NK cell immunotherapy—A scientometric analysis - Chen, Li; Cheng, Lin (Frontiers in Immunology, 2025)
BackgroundPsoriasis is a chronic, relapsing, immune-mediated skin disease with a complex pathogenesis and significant individual variability in treatment response. It is characterized by a high relapse rate. In recent years, the critical role of natural killer (NK) cells in the onset and relapse of psoriasis has increasingly attracted attention, and related immune intervention strategies have become a research hotspot.ObjectiveThis study aims to systematically review the research progress in the field of “NK cells and psoriasis” using bibliometric methods. It identifies research hotspots and key trends, constructs the knowledge structure of this field, and provides data support for related mechanistic studies and clinical translation.MethodsBased on the Web of Science Core Collection and PubMed databases, we retrieved relevant English-language literature from 2000 to 2025. Using tools such as CiteSpace and VOSviewer, we conducted keyword clustering, author and institutional collaboration analysis, journal co-citation analysis, and highly cited literature mining to create knowledge maps.ResultsA total of 432 publications were included, with a sustained increase in the number of publications over time. The United States, China, and Germany were the main contributing countries, while Rockefeller University and Karolinska Institute were core institutions. The journal Frontiers in Immunology was identified as an important publication venue. Current research focuses on three hotspots: (1) the role of tissue-resident NK cells in “trained immunity” during psoriasis relapse; (2) metabolic reprogramming of NK cells in lesions, with a close correlation between their metabolic status and pro-inflammatory functions; and (3) the development of NK cell-targeted therapeutic strategies, such as dimethyl fumarate (DMF) and IL - 23 inhibitors, which show promising prospects.ConclusionThis study constructed a comprehensive knowledge map of “NK cells–psoriasis” research, clarifying the hotspots and structural characteristics. Future research will focus on two trends: (1) exploring the pivotal role of NK cells in multi-systemic immune comorbidities and (2) developing specific intervention strategies for different stages of disease progression to advance the development of precision immunotherapy for psoriasis.